Changes in muscle activity during karate guiaku-zuki-punch and kiza-mawashi-guiri-kick after specific training in elite athletes - Jemili, H.; Mejri, M. Arbi; Sioud, R.; Bouhlel, E.; Amri, M. (Science & Sports, 2017)
Objective: Was to investigate the effect of 3-month karate training on electromyographic activity (EMG) of guiaku-zuki-punch and kiza-mawashi-guiri-kick in elite karatekas. Material and methods: Thirteen male elite karatekas have participated in this study. We have measured the EMG activity of the biceps and triceps brachii during guiaku-zuki and the biceps and rectus femoris during kiza-mawashi-guiri of the right side before (T0) and after 3-month intense karate training (T1). Results: We found an increase in root mean square (RMS) values of the biceps and triceps brachii associated with increases in signal's amplitude and a significant decrease of the onset muscle activation time of the biceps brachii (P < 0.0005) after training. In addition, the EMG analysis of guiaku-zuki showed an activation of big size motor units regardless of the training, whereas medium and small size motor units appeared only after training (T1). We found significant decrease in activation time of the rectus femoris (P < 0.05) and a decrease in the onset muscle activation time of the biceps and rectus femoris (P < 0.0005) in T1. Conclusion: A 3-month karate training induced changes in neuromuscular activation strategy. The higher muscle activation during guiaku-zuki explains the enhancement of motor unit recruitment. The reduction in the onset of activation time after training indicates better coordination between agonist and antagonist muscles to stabilize and control the movement during punches and kicks in our athletes.